Cortical Bone Thickness, Base Osteophyte Occurrence and Radiological Signs of Osteoarthritis in the Fingers of Male Elite Sport Climbers: A Cross-Sectional 10-Year Follow-Up Study - Pastor, Torsten; Fröhlich, Stefan; Pastor, Tatjana; Spörri, Jörg; Schweizer, Andreas (Frontiers in Physiology, 2022)
Background: Sport climbing places high mechanical loads on fingers. In 2012, our research group demonstrated adaptations of climbers’ cortical bones with presence of osteophytes compared to a non-climbing control group. Objectives: (1) To investigate 10-year changes in cortical bone thickness, base osteophyte occurrence and radiological signs of osteoarthritis in fingers of elite male sport climbers with more than 25years of climbing history and (2) to compare cortical bone thickness, base osteophyte occurrence and radiological signs of osteoarthritis between male sport climbers and age-matched controls at the 10-year follow-up. Methods: All 31 elite sport climbers who participated in both baseline and 10-year follow-up assessments (follow-up rate 100%) were examined by means of X-rays. Cortical bone thickness, presence of osteophytes and signs of osteoarthritis according to Kellgren-Lawrence were obtained and compared to the baseline values 10years earlier and to an age-matched control group at the follow-up (n=15). Results: Significantly increased cortical bone thickness over the past 10years was observed in the climber group (mean absolute difference with 95% CI:0.98mm (0.77mm, 1.19mm);p<0.001). Moreover, compared to age-matched controls, climbers had significantly thicker cortical bone at the 10-year follow-up (mean absolute difference with 95% CI:0.86mm (0.61mm, 1.12mm);p<0.001). In climbers, osteophytes and clear signs of osteoarthritis were mainly seen in DIP joints. Signs of osteoarthritis according to Kellgren-Lawrence were more prevalent than 10years before in most joints. In lateral radiographs, base osteophytes were not significantly more prevalent than 10years before in most of the joints. The percentage of climbers who had osteophytes in any DIP (PIP) joint increased from 93.5% (67.7%) at baseline to 100% (74.2%) at 10-year follow-up. The percentage of climbers who had clear signs of osteoarthritis according to Kellgren-Lawrence in any DIP (PIP) joint increased from 12.9% (9.7%) at baseline to 74.2% (64.5%) at 10-year follow-up. Only a few such degenerative changes were found in age-matched controls. Conclusion: An accumulation of repetitive climbing-related stress to the fingers of elite sport climbers over the career may induce lifelong mechano-adaptation of the cortical bone thickness of all phalanges. At the 10-year follow-up, a further significant increase in radiographic signs of osteoarthritic changes was observed.